A comprehensive approachfor off-road trafficability evaluation and development of modified equation for estimation of RCI to assessregional soil variation using geospatial technology - Sunil Kumar Pundir; Rahul Dev Garg (Quaternary Science Advances, 2022)
The information of terrain is highly valuable as the accuracy of decision maker depends on input data for taking the correct decision. For planning of any successful off-road movement, the terrain information plays the vital role. This paper describes the state of art of off-road trafficability leading from the contributing factors, Instruments for measurements and trafficability mapping techniques in chronological order. In modern times, the number & type of tracked or wheeled vehicles, has increased many times, therefore off-road trafficability for operation planning became a complex task to handle. The accuracy and reliability of measurements involved in trafficability will play a major role for any successful operation. Off-road trafficability shows the capacity of soil required for vehicular movement. Remolding Cone Index (RCI) indicates the soil's capability for off-road movement. In this study, the area was divided in equal small grids for ease of computation of RCI. Geospatial technology provides the platform to determine the locations of observation points as well as the extrapolation of information of inaccessible area using geospatial tools and techniques. RCI values were computed for each grid and also measured with cone penetrometer in the field. R2 value for observation values was determined for different soils present in the area to check the accuracy of measurements and then based on observed value and computed value, R squared (coefficient of determination) values (0.7754 and 0.4867) were evaluated for both study areas to get the idea about relevance, reliability and accuracy. Residual RCI (RRCI), difference of computed & observed was also analyzed for different soils for different moisture conditions. Based on thisanalysis, a modified equation was developed for different type of soils present in the study area. This development will pave the way to compute the RCI accurately, which will be used to assess the off-road trafficability of other areas in similar manner. Therefore, this study is useful to assess the regional variation of soil behavior towards trafficability based on modified equation.